THE EFFECTIVENESS OF LAND AND BUILDING TAX (PBB) INCENTIVES IN MAKASAR CITY - Dermayasair, Indirwan; Husen, La Ode; Hasyim, Satri (IBLAM LAW REVIEW, 2023)
This research was conducted with the objectives of (1) To find out and analyze the effectiveness of giving Land and Building Tax (PBB) incentives in Makassar City, (2) To analyze the Implementation of Land and Building Tax (PBB) Incentive Policies in Makassar City. The research method used in this study is an empirical juridical approach, which examines the legal provisions that apply in society. Data collection is done through observation, interviews, and documentation. This study analyzes the effectiveness of providing land and building tax incentives with a ratio approach and the effectiveness theory. The data used are the results of interviews and data on the provision of tax incentives in 2020. Based on the results of the research conducted, the researchers concluded that the level of effectiveness in providing tax incentives is not yet effective because the results of a comparison of taxpayers who take advantage of tax incentives are still very small compared to the number of taxpayers in cities. Makassar, or only 1.65% of the total 356,130 taxpayers, only 5,881 took advantage of tax incentives. Obstacles found in this study are the ineffectiveness of communication and socialization and the existence of restrictions on social interaction, and adaptation in the organizational environment.